Book Review. Finding a New Prism of Understanding the “Papua Conflict” Through Papua’s Insecurity: State Failure in the Indonesian Periphery - Maretta Kartika Sari (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2017)
Another international published research voicing yet the Papua quandary was written by author Bobby Anderson, a non-Indonesian research worker who has been conducting much work in the area. Published in 2015, Papua’s Insecurity: State Failure in the Indonesian Periphery is part of the Policy Studies series, an ongoing publication project by the U.S.-based education and research institution of the East-West Center. Issues of the series are based on fieldwork and academic study, that aim primarily to provide new perspectives and insights on stakeholders’ policies—and in the context of this particular publication, those in the Papua region. It is also noteworthy that the series, tallying to the platform of the above-stated organization, cover the areas of Asia and have target readers comprised particularly of policy and business communities, academics, journalists, and the informed public who probably also hold a special interest in the relations between the U.S. and the region.